Optimal Macroprudential Policy and Asset Price Bubbles - Biljanovska, Nina.; Gornicka, Lucyna; Vardoulakis, Alexandros (Washington, D.C. : International Monetary Fund, 2019)
An asset bubble relaxes collateral constraints and increases borrowing by credit-constrained agents. At the same time, as the bubble deflates when constraints start binding, it amplifies downturns. We show analytically and quantitatively that the macroprudential policy should optimally respond to building asset price bubbles non-monotonically depending on the underlying level of indebtedness. If the level of debt is moderate, policy should accommodate the bubble to reduce the incidence of a binding collateral constraint. If debt is elevated, policy should lean against the bubble more aggressively to mitigate the pecuniary externalities from a deflating bubble when constraints bind.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet